Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 3475 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Camelus dromedarius", "Geometry POLYGON((107.58 -39.81,107.58 -8.46,162.69 -8.46,162.69 -39.81,107.58 -39.81))", "HasGeospatialIssue is false", "Year 1600-2017" ] } The dataset includes 3475 records from 6 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0052784-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences